Pengaruh Pemberian Tepung Pupa Maggot Black Soldier Fly (BSF) pada Pakan Jadi Komersial terhadap Performa Ayam Kampung Unggul Balitbangtan (Kub) Fase Starter - Rizal Luqmanudin; Ali Mursyid Wahyu Mulyono (Bantara Journal of Animal Science, 2026)
This study aims to evaluate the effect of Black Soldier Fly (BSF) maggot meal substitution in commercial feed on the performance of starter phase Balitbangtan Superior Native Chicken (KUB) aged 1–5 weeks. The research method used was experimental with a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications. The treatments included P0 (control without maggot meal), P1 (1% maggot meal), P2 (2% maggot meal), and P3 (3% maggot meal). The parameters observed were feed intake, average daily gain (ADG), and Feed Conversion Ratio (FCR). The results showed that the highest average ADG was found in P3 (289.23 g) and the lowest in P1 (232.47 g). Average feed intake from 654.54 to 664.99 g, while the most efficient FCR value was found in P3 (2.29). However, statistical analysis revealed that the addition of maggot meal up to 3% did not have a significant effect ($P>0.05$) on all observed performance parameters. The conclusion of this study is that the use of BSF maggot meal as a substitute for Multifeed BR 1-7 RT commercial feed at levels of 1–3% can maintain the performance of KUB chickens but has not been able to significantly increase growth.